(untitled) (Research, Society and Development, 2022)
The coexistence between men and animals has existed since the beginning, and this interaction has grown a lot in recent years. Although, in the past, the animal was used only for grazing and guarding in the rural community, it is possible today to observe them living with people inside their homes and being considered family members, in the city and in the countryside. In this context, this study aimed to evaluate the interference of domestic animals in stimulating the mobility of people living in a city in the interior of Rio Grande do Sul. For this purpose, a descriptive observational design of qualitative analysis was used. 19 tutors participated in this research, selected from the vaccination record of a veterinary service, in the second quarter of 2019. These employees, aged between 22 and 75 years, identified themselves as 15 female and four males; mentioned several marital arrangements, predominantly married. Through a semi-structured interview, audio-recorded and later transcribed in textual form, a content analysis was carried out to discuss the results. Where five categories of analysis are distinguished: Motivation in the acquisition of the pet, interaction, feeling, perception of health and mobility. It is observed in the outcome of the study that the pet is part of people’s daily routines, and its influence is essential in several aspects, especially regarding mobility, since the inclusion of the pet in family life brings responsibilities due to care and generates greater movement to perform them, a fact observed with children, adults, and the elderly.